Energy Efficient MAC for QoS Traffic in Wireless Body Area Network - Anil K. Jacob; Lillykutty Jacob (International Journal of Distributed Sensor Networks)
Lifetimes and latencies of devices in wireless body area networks (WBANs) that monitor the health conditions of patients largely determine their utility under such a setup. It is seen that the medium access method used in the body area network can play a significant role in determining the quality of service such medical devices can provide. IEEE 802.15.6 standard for WBAN includes different types of medium access, namely, CSMA/CA, scheduled, and polling access schemes, or a combination of these techniques. In this paper, medium access methods proposed in IEEE 802.15.6 standard are investigated to assess their effectiveness in meeting the lifetime and quality of service requirements of WBANs. We then propose sleeping schedules for contention and polling access schemes to extend the device lifetime. Simulation studies are done for the investigation using a typical configuration of the medical devices found in a hospital setting. It is found that priority polling technique can give a combination of high lifetime and a low latency. Various other results offer important insights into the behaviour of these techniques under WBAN conditions.